Beneficial effects of novel strains of Aureobasidium pullulans produced 1,3-1,6 β-glucans on non-esterified fatty acid levels in diabetic KKAy mice - Ikewaki, Nobunao; Onaka, Takashi; Ikeue, Yasunori; Nagataki, Mitsuru; Kurosawa, Gene; Vidyasagar Devaprasad Dedeepiya; Rajmohan, Mathaiyan; Vaddi, Suryaprakash; Senthilkumar, Rajappa; Senthilkumar Preethy; Abraham, Samuel Jk (bioRxiv, 2021)
Obesity, metabolic syndrome, associated lipotoxicity and its cascade of events contribute to the majority of the burden related to non-communicable diseases globally. Preventive lifestyle changes aside, several beneficial effects have been reported in type II diabetes mellitus and dyslipidaemia patients with biological response modifier glucans (BRMG) produced as an exopolysaccharide by Aureobasidium pullulans. In this study, we compared two strains (AFO 202 and N 163) that produce beta glucans in alleviating lipotoxicity. This study was performed in obese diabetic mice model of KKAy mice, in four groups with six subjects in each group Group 1: sacrificed on Day 0 for baseline values; Group 2: control (drinking water); Group 3: AFO 202 beta glucan 200 mg/kg/day; Group 4: N 163 beta glucan 300 mg/kg/day. The animals in groups 2 to 4 had the test solutions administered by gavage once daily for 28 consecutive days. Biochemical analyses were conducted of blood glucose, triglycerides, total cholesterol, LDL cholesterol, HDL cholesterol and non-esterified fatty acids (NEFA). Group 4 (N 163) had the lowest NEFA levels, as compared to the other groups, and marginally decreased triglyceride levels. The groups had no significant differences in blood glucose, HbA1c, triglycerides, or LDL and HDL cholesterol. N-163 produced by A. pullulans decreased NEFA in a diabetic mice model in 28 days. These results, although modest, warrant further in-depth research into lipotoxicity and associated inflammatory cascades in both healthy and disease affected subjects to develop novel strategies for prevention and management. Competing Interest Statement 1. Author Samuel Abraham is a shareholder in GN Corporation, Japan which in turn is a shareholder in the manufacturing company of the Beta Glucans described in the study. 2. Author Takashi Onaka is a shareholder and Yasunori Ikeue is member of the board in the manufacturing company of the Beta Glucans described in the study.